2019
DOI: 10.3390/antibiotics8020050
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FDA-Approved Drugs with Activity against Stationary Phase Bartonella henselae

Abstract: Bartonella henselae can cause various infections in humans, ranging from benign and self-limiting diseases to severe and life-threatening diseases as well as persistent infections that are difficult to treat. To develop more effective treatments for persistent Bartonella infections, in this study, we performed a high-throughput screen of an FDA-approved drug library against stationary phase B. henselae using the SYBR Green I/propidium iodide (PI) viability assay. We identified 110 drug candidates that had bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(57 citation statements)
references
References 51 publications
4
53
0
Order By: Relevance
“…Based on the culture medium developed in a previous study [57], B. henselae JK53 was cultured in Schneider's Drosophila medium (Life Technologies Limited, Paisley, UK) supplemented with 10% fetal bovine serum (FBS) (Sigma-Aldrich, Co., St. Louis, MO, USA) and 5% sucrose (Fisher Scientific, New Jersey, USA) in microaerophilic incubator without shaking at 37°C, 5% CO 2 . As previously measured [24], B. henselae JK53 rapidly went into the logarithmic growth phase and reached a growth peak after two days under such culture conditions. The one-day-old and five-day-old culture were considered as log phase and stationary phase, respectively.…”
Section: Bacterial Strain Culture Media and Culture Conditionssupporting
confidence: 78%
See 3 more Smart Citations
“…Based on the culture medium developed in a previous study [57], B. henselae JK53 was cultured in Schneider's Drosophila medium (Life Technologies Limited, Paisley, UK) supplemented with 10% fetal bovine serum (FBS) (Sigma-Aldrich, Co., St. Louis, MO, USA) and 5% sucrose (Fisher Scientific, New Jersey, USA) in microaerophilic incubator without shaking at 37°C, 5% CO 2 . As previously measured [24], B. henselae JK53 rapidly went into the logarithmic growth phase and reached a growth peak after two days under such culture conditions. The one-day-old and five-day-old culture were considered as log phase and stationary phase, respectively.…”
Section: Bacterial Strain Culture Media and Culture Conditionssupporting
confidence: 78%
“…Previously, we have developed an SYBR Green I/PI viability assay for the rapid viability assessment of B. henselae and have successfully used this assay for high-throughput drug screens against non-growing stationary phase B. henselae using the FDA drug library [24]. Here we adapted this SYBR Green I/PI viability assay for essential oil screens against B. henselae.…”
Section: Subsection Screening Essential Oil Collection To Identify Drmentioning
confidence: 99%
See 2 more Smart Citations
“…We speculated that PP inhibited the growth of M. tb by suppressing NAD+/NADH conversion within the bacteria, but this requires further experimental validation. Recently, some studies reported that PP had pharmacological activity to inhibit the growth of Bartonella henselae infection [32] and coronaviruses replication in vitro [33,34]. PP has also been reported to have anti-tumor activity [28,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%